A new rejuvenating technique for cable localized insulation failures of railway locomotives. Issue 2 (April 2021) - Jia, JinJun; Zhao, YongXiang; Wang, JunGou; Liu, ZhiWei
Abstract: A new rejuvenating technique, injection plastic technique with standard scales and over coatings, is developed for restoring the localized cable insulation failures of railway locomotives. The materials of cable jacket and insulation layers are pelt with standard scales around the localized fault location. The failed materials are treated visibly to eliminate hidden perils. Matched moulds with over coating spaces are creatively designed and manufactured for rejuvenating cable insulation and jacket layers materials with injection moulding machine. The policies of standard scales and over coatings can well ensure a reliable rejuvenation, good bound seals and well economic benefits.